ERLINDUNGAN HUKUM BAGI INVESTOR ASING DI INDONESIA - Mutia Evi Kristhy; Meishy Febrizha; Okto Rianto Saputra Satya; Linda Kumala; Pardomuan Putra Ande; Noor Hidayah (Jurnal Komunikasi Hukum, 2022)
Investment is an exertion to save or place finances for a certain period with the stopgap that the deposit will induce gains or increase the value of the investment. Investment is nearly related to business, but beyond that there are numerous investments that aren't business-bound. There are numerousnon-business investments that have lately been attracted by the public with the end of adding the value of their means. An investment always involves spending a certain quantum of capital moment starting from time, trouble, plutocrat, or means with the stopgap of lesser returns in the future. So simply, the notion of investment is developing plutocrat or other means in order to give benefits in the future to achieve certain pretensions. Foreign Direct Investment, which is an investment or investment forming from foreign or foreign parties. In short, the meaning of FDI is foreign investment or foreign investment. Generally, the purpose of doing FDI is to gain a continuing interest, where the relationship between foreign investors and companies occurs on a long- term base, and so that investors can see the significant influence of investors on company operation. FDI can be carried out by individualities or foreign companies from abroad. FDI is also a medium or tool in a global profitable system, but investment isn't made through the stock exchange.